Philosophy of Science Meets the Scientific Research: Metatheorizing expertise theories in Cognitive Psychology - Alireza Monajemi (University of Tabriz, 2021)
An obvious feature of the development of the philosophy of science during the past decades is an increasing specialization and fragmentation that have led to reduced impact of philosophy of science outside the sphere of its own discipline. It seems that philosophy of science and scientific research are moving away from each other. The major question of this article is how can reconnect these two?To answer this question I will try to highlight some events especially in the fields of social sciences that researchers are involved in discussions, generally related to philosophy of science, not in an abstract and isolated way, but in a way that is completely intertwined in their research practices.  Unfortunately, this phenomenon has not been properly considered by philosophers of science and has remained more as a subject in the field of social sciences, specifically research methodology. It seems that if philosophy of science enters into dialogue with social sciences, we can expect the revival of the philosophy of general science. In this article, I try to show the signs of this phenomenon in cognitive psychology. I will first turn to one of the most influential theories in the cognitive sciences, expertise theory. After reviewing the important theories of expertise and their differences, in the next step I will discuss the seemingly opposing theories in this field and their efforts to find common ground. Then I will review the current movement in cognitive psychology, which I call the “integration model” stream. After a critical review and categorization of these models, I will show that in a broader view in social science, we can realize the meta-theoretical issues that are a good room for a dialogue between philosophy of science and scientific research. In the end, I will point out the horizons that this view opens to the revival of philosophy of general science.